Multiplying a Monomial by a Monomial

1. Multiplying Two Monomials

While multiplying two polynomials the resultant variable will come by

  • The coefficient of product = Coefficient of the first monomial × Coefficient of the second monomial
  • The algebraic factor of product = Algebraic factor of the first monomial × Algebraic factor of the second monomial.

Example

25y × 3xy = 125xy2

2. Multiplying Three or More Monomials

While multiplying three or more monomial the criterion will remain the same.

Example

4xy × 5x2y2 × 6x3y3 = (4xy × 5x2y2) × 6x3y3

= 20x3y3 × 6x3y3

= 120x3y3 × x3y3

= 120 (x3 × x3) × (y3 × y3)

= 120x6 × y6

= 120x6y6

OR

4xy × 5x2y2 × 6xy3

= (4 × 5 × 6) × (x × x2 × x3) × (y × y2 × y3)

= 120 x6y6

Scroll to Top